White Matter Abnormalities Associated With Prolonged Recovery in Adolescents Following Concussion - Lima Santos, João Paulo; Kontos, Anthony P.; Mailliard, Sarrah; Eagle, Shawn R.; Holland, Cynthia L.; Suss, Stephen J.; Abdul-waalee, Halimah; Stiffler, Richelle S.; Bitzer, Hannah B.; Blaney, Nicholas A.; Colorito, Adam T.; Santucci, Christopher G.; et al. (Frontiers in Neurology, 2021)
Background: Concussion symptoms in adolescents typically resolve within 4 weeks. However, 20 – 30% of adolescents experience a prolonged recovery. Abnormalities in tracts implicated in visuospatial attention and emotional regulation (i.e., inferior longitudinal fasciculus, ILF; inferior fronto-occipital fasciculus, IFOF; uncinate fasciculus; UF) have been consistently reported in concussion; yet, to date, there are no objective markers of prolonged recovery in adolescents. Here, we evaluated the utility of diffusion MRI in outcome prediction. Forty-two adolescents (12.1 – 17.9 years; female: 44.0%) underwent a diffusion Magnetic Resonance Imaging (dMRI) protocol within the first 10 days of concussion. Based on days of injury until medical clearance, adolescents were then categorized into SHORT (<28 days; N = 21) or LONG (>28 days; N = 21) recovery time. Fractional anisotropy (FA) in the ILF, IFOF, UF, and/or concussion symptoms were used as predictors of recovery time (SHORT, LONG). Forty-two age- and sex-matched healthy controls served as reference. Higher FA in the ILF (left: adjusted odds ratio; AOR = 0.36, 95% CI = 0.15 – 0.91, P = 0.030; right: AOR = 0.28, 95% CI = 0.10 – 0.83, P = 0.021), IFOF (left: AOR = 0.21, 95% CI = 0.07 – 0.66, P = 0.008; right: AOR = 0.30, 95% CI = 0.11 – 0.83, P = 0.020), and UF (left: AOR = 0.26, 95% CI = 0.09 – 0.74, P = 0.011; right: AOR = 0.28, 95% CI = 0.10 – 0.73, P = 0.010) was associated with SHORT recovery. In additional analyses, while adolescents with SHORT recovery did not differ from HC, those with LONG recovery showed lower FA in the ILF and IFOF (P < 0.014). Notably, inclusion of dMRI findings increased the sensitivity and specificity (AUC = 0.93) of a prediction model including clinical variables only (AUC = 0.75). Our findings indicate that higher FA in long associative tracts (especially ILF) might inform a more objective and accurate prognosis for recovery time in adolescents following concussion.